Evaluating the Impact of a New Smartphone Texting Tool on Patient Care in Obstetrics, an Emergent Healthcare Setting - Feinberg, Jacqueline; Shaw, Sara; Kashyap, Nitu; Illuzzi, Jessica; Campbell, Katherine; Hsiao, Allen L.; Pettker, Christian M. (Applied Clinical Informatics, 2019)
Background Hospitals across the country are investing millions of dollars to adopt new Health Insurance Portability and Accountability Act (HIPAA)-compliant secure text messaging systems. However, in nearly all cases, these implementations are occurring without evaluation of their impact on patient care.Objective To evaluate perceived impact on patient care and workflow of new text messaging system implemented in obstetrics at Yale-New Haven Hospital and to inform guidelines for future implementations in emergent settings.Methods A new HIPAA-compliant texting system was implemented in obstetrics in 2016. Before implementation of the new system, residents and nurses were surveyed on perceived effect of communication system (pagers with text receiving, service mobile phones, personal cell phones) on clinical workflow and patient care using 5-point Likert scale and open-ended questions. Following roll-out (1 and 6 months), both teams were surveyed with same questions. Results were compared using Wilcoxon–Mann–Whitney test (0–1 months and then 0–6 months). Open-ended question results were qualitatively compared for recurrent unifying themes.Results In both nursing and resident domains, 1 month after implementation, the new communication system was perceived to significantly improve efficiency and patient care across all metrics. After 6 months, this effect decayed in nearly all categories (including efficiency, real-time communication, and knowledge of covering provider). The exception was nurse's knowledge of which resident to contact and resident's timely evaluation of patient, for which we observed sustained improvements. System shortcomings identified included interrupted connection (i.e., dropped calls), dysfunctional and inaccurate alert system, and unclear identification of the covering provider.Conclusion A new text-messaging–based communication system may improve efficiency and patient care in emergent settings, but system shortcomings can substantially erode potential benefits over time. We recommend implementers evaluate new systems for a set of specific functional requirements to increase probability of sustained improvement and decrease risk of poor patient outcomes.
Keywords: text messaging; smart phone; hospital system; obstetrics